If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2 = 2y + 13 Reorder the terms: 2 + 3y = 2y + 13 Reorder the terms: 2 + 3y = 13 + 2y Solving 2 + 3y = 13 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 2 + 3y + -2y = 13 + 2y + -2y Combine like terms: 3y + -2y = 1y 2 + 1y = 13 + 2y + -2y Combine like terms: 2y + -2y = 0 2 + 1y = 13 + 0 2 + 1y = 13 Add '-2' to each side of the equation. 2 + -2 + 1y = 13 + -2 Combine like terms: 2 + -2 = 0 0 + 1y = 13 + -2 1y = 13 + -2 Combine like terms: 13 + -2 = 11 1y = 11 Divide each side by '1'. y = 11 Simplifying y = 11
| -1/5b-2/5=-5 | | 250/298=x/368 | | -12a+8=-28 | | N+-4=-11 | | (32b)^(2/3) | | 3•5/13 | | (3x+5)(5x-2)=0 | | 4+2(7r-4)=-116 | | 2=0.15x^2+1 | | (((2z)^(1/5))^4)/(z^(1/20)) | | 4+2(7r-r)=-116 | | 5=0.55x^2+1 | | (((2z)^(1/5))^4)/z^(1/20) | | 2.70=0.55x^2+1 | | -2x-3y=-5 | | -5(4n-4)=40 | | -5h=-20 | | 4(x-1)=2(-x) | | 4p^2+11p-45=0 | | 6(2v-2)=96 | | 40b+10=210 | | (2x+10)+5x+140= | | 3(8-4x)=84 | | 4x-13-35=0 | | 3x+90=450 | | 2(x+5)(x-1)= | | 7+9+n=-9+2n+n | | 4*x^2+4*y^2-y^3=0 | | 4c-36=-8 | | y+26-8=40 | | 93=16-5p | | -12x-4=56 |